PENGARUH KOMPENSASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BINA MARGA PROPINSI SULAWESI TENGAH - Muliati, Muliati (Katalogis, 2014)
This study aimed to understand and analyze the simultaneous effect of compensation, work discipline,  and  work  environment  on  employee’s  performance  at  Bina  Marga  Agency  in  the Province of Central Sulawesi. It also analyzed partial effect of compensation on employee’s performance, work discipline on employee’s perfomance and work environment on employee’s perfomance at Bina Marga Agency in Central Sulawesi Province, The sample of the study was 115 employees which were scattered on each woork unit within Bina Marga Agency. Study utilized descriptive-verification reseacrh method with multiple linear regressions. Study results show that the variables namely compensation, work discipline, and work environment simultaneously have significant effect on employee’s performance. Each dependent variable has also significant effect on employee’s performance.